Virucidal efficacy of different formulations for hand and surface disinfection targeting SARS CoV-2. (June 2021) - Steinhauer, K.; Meister, T.L.; Todt, D.; Krawczyk, A.; Paßvogel, L.; Becker, B.; Paulmann, D.; Bischoff, B.; Eggers, M.; Pfaender, S.; Brill, F.H.H.; Steinmann, E.
Summary: In the ongoing SARS CoV-2 pandemic, effective disinfection measures are needed, and guidance based on the methodological framework of the European Committee for Standardization (CEN) may enable the choice of effective disinfectants on an immediate basis. This study aimed to elucidate whether disinfectants claiming 'virucidal activity against enveloped viruses' as specified in the European Standard EN 14476 as well as in the German Association for the Control of Viral Diseases/Robert Koch Institute (DVV/RKI) guideline are effectively inactivating SARS-CoV-2. Two commercially available formulations for surface disinfection and one formulation for hand disinfection were studied regarding their virucidal activity. Based on the data of this study the enveloped SARS-CoV-2 is at least equally susceptible compared to the standard test virus vaccinia used in the EN 14476 and DVV/RKI guidelines. Thus, chemical disinfectants claiming 'virucidal activity against enveloped viruses' based on the EN 14476 and DVV/RKI guidelines will be an effective choice to target enveloped SARS-CoV-2 as a preventive measure.